HEAT TRANSFER OF CYLINDER BEING COAXIAL WITH EFFECTIVE VOLUME OF CYCLONE CHAMBER WITH DOUBLE ASYMMETRICAL GAS INLET - N. N. Gushchina; A. A. Niyazmatov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
Investigation of heat transfer on the surface of a circular cylinder with asymmetrical gas inlet  conditions in  a  cyclone chamber  has been executed while changing an aggregate state of heating agent  that is slightly superheated steam which is supplied  into the cylinder-calorimeter. Air has been supplied into the cyclone chamber  from  two diametrically opposite sides through  the slots in the top and bottom parts of the transverse planes on  a  relative distance from the ends which is equal to 0,5Dк. Unbalanced stream input into the chamber has been created  due to varying  the inlet relative area  in  its  bottom  part.  The obtained  data have been processed  in the  form of dependence of the average Nusselt number on Re number and a parameter characterizing the asymmetry of the inlet.